Pandemia por COVID-19, una mirada desde la cosmovisión andina en la comunidad indígena de Saraguro, período octubre 2022- febrero 2023 - Torres Abrigo, Sharon Gabriela (2024)
The COVID-19 pandemic affected different scenarios worldwide; however, influenced by culture and customs, it was experienced and perceived differently in indigenous communities. In this sense, the aim of this research was to characterise the COVID-19 pandemic from the Andean cosmovision in the indigenous community of Saraguro. Methodologically, it was a qualitative study with a phenomenological design, in which 10 people participated; a semi-structured interview technique was used to collect the data, organising the information into three categories. The results showed that in the first category of perception, the participants consider that the pathology originated in China, that the disease is transmissible and fatal, and that they have made use of biosecurity measures. In relation to the second category related to the experiences, it was found that within the most common clinic the participants presented general body discomfort, they also used the symptoms as a method of diagnosis, regarding the handling of corpses they changed the way they performed their rituals; on the other hand, as prevention measures the entrance and exit of the villagers was restricted, moreover, the majority of the population did not go to the health centres of their own free will, they also did not accept the application of the vaccine and only two people used pharmacological treatment. Finally, in the third category related to the treatment of the diseases, ancestral practices were used where eucalyptus, cascarilla, orange and ginger were used. In conclusion, the COVID-19 pandemic had particular characteristics due to the culture of the indigenous community of Saraguro from the different categories addressed, which had an impact on the way in which people perceive the disease and how they use ancestral medicine for the maintenance of health